Penggunaan Deep Learning dalam Pembelajaran Berbasis Proyek untuk Pengembangan Karakter: Sebuah Tinjauan Pustaka Sistematis - Mardatillah, Bella; Wulandari, Imas; Zulfianti, Heri Maria (Dawuh Guru: Jurnal Pendidikan MI/SD, 2025)
This research aims to analyze the implementation of deep learning models to optimize project-based learning for Pancasila Student Profile in elementary schools, particularly in character development for grade IV-VI students. The research method uses a qualitative approach with systematic literature review on project-based learning, intelligent learning technology, and character development. The results show that project-based learning is effective in instilling Pancasila values through practical activities that actively involve students. Digital technology implementation in learning has positive impact on improving critical thinking skills, creativity, and student collaboration abilities. The learning model developed with eight ideal syntax proves to be effectively implementable with expert validation support. Implementation challenges include lack of parental support and resource limitations, but can be overcome through collaboration between schools, parents, and community. The research recommends strengthening teacher mentoring, improving digital content quality, developing comprehensive evaluation systems, and utilizing local potential in learning project design for long-term program optimization.